Neurons with larval synaptic targets pioneer the later nervous system in the annelid Malacoceros fuliginosus - Anna Seybold; Anna Seybold; Suman Kumar; Suman Kumar; Sharat Chandra Tumu; Harald Hausen; Harald Hausen (Frontiers in Neuroscience)
Comparative studies on the development of nervous systems have a significant impact on understanding animal nervous system evolution. Nevertheless, an important question is to what degree neuronal structures, which play an important role in early stages, become part of the adult nervous system or are relevant for its formation. This is likely in many direct developers, but it is not the case in forms with catastrophic metamorphosis. It is not clear in many forms with gradual metamorphosis. This introduces uncertainty in tracing the evolution of nervous systems and of larval forms. One of the prominent larval characteristics of numerous planktonic marine organisms is the epidermal ciliation used for swimming and steering, which disappears during metamorphosis. Therefore, the neuronal elements controlling the ciliary beating are often assumed to vanish with the cilia and regarded as purely larval specializations. With volume EM, we followed the neuronal targets of the very first pioneer neurons at the apical and posterior ends of the larva of the annelid Malacoceros fuliginosus. We observed that all of these pioneers appear to have a dual function. Although they are laying the paths for the later adult nervous system, they also make synaptic contact with the main ciliated ring of the larva. We propose that the formation of the later adult nervous system and the innervation of the larval locomotory organ are indeed closely linked to each other. This has implications for understanding the early nervous system development of marine larvae and for existing hypotheses on nervous system evolution.